2021
DOI: 10.1038/s41467-021-24189-3
|View full text |Cite
|
Sign up to set email alerts
|

Topological phases and bulk-edge correspondence of magnetized cold plasmas

Abstract: Plasmas have been recently studied as topological materials. However, a comprehensive picture of topological phases and topological phase transitions in cold magnetized plasmas is still missing. Here we systematically map out all the topological phases and establish the bulk-edge correspondence in cold magnetized plasmas. We find that for the linear eigenmodes, there are 10 topological phases in the parameter space of density n, magnetic field B, and parallel wavenumber kz, separated by the surfaces of Langmui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 32 publications
0
54
0
Order By: Relevance
“…Surface waves in plasmas have been extensively studied [1-3] due to their wide range of applications [4][5][6][7][8][9]. Recently, a new class of surface modes in plasma produced by topological phase transition have been investigated [10,11]. Here, we report studies on the dispersion and propagation of the newly identified topological surface mode called Topological Langmuir-Cyclotron Wave (TLCW) in cold magnetized plasmas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface waves in plasmas have been extensively studied [1-3] due to their wide range of applications [4][5][6][7][8][9]. Recently, a new class of surface modes in plasma produced by topological phase transition have been investigated [10,11]. Here, we report studies on the dispersion and propagation of the newly identified topological surface mode called Topological Langmuir-Cyclotron Wave (TLCW) in cold magnetized plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…When variation in the z-direction can be ignored, i.e., k z = 0, Chern numbers for the X waves in 2D plasmas were calculated [34,35] and related to surface waves via the bulk-edge correspondence [36]. When k z = 0, the non-trivial topology of the plasma as a 2D system were found [10,37] and its topological phase diagram was established [11]. In particular, underdense plasmas can be regarded as a Weyl semimetal [38,39] and host a surface state with the Fermi-arc structure [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here subscript x, y, z show the component of electromagnetic fields in x−, y− and z− direction, (1-4) over the PVI. For low frequency SPW's on SPVI, transverse permittivity t remains positive everywhere and the waves propagate without damping [11,12]. The boundary conditions turn out to be…”
mentioning
confidence: 99%
“…Recently, topological properties of edge states (surface plasma waves; SPW's), occurring at the boundary of cold magnetized plasma, have been explored [8][9][10][11][12][13] and it has been shown that for certain choices of plasma density (n), stationary external magnetic field (B 0 = B 0 ẑ) and parallel wavenumber k z , SPW's can exist at the plasma-vacuum [11] or plasma-plasma interface, provided both plasmas have different topological phase [12].…”
mentioning
confidence: 99%